Islamic Values in Mottainai Philosophy and Osagari Tradition in Japan - Ade Tuti Turistiati (IBDA': Jurnal Kebudayaan Islam, 2019)
Prices of goods in Japan are relatively expensive. Meanwhile, to dispose of used or second hand goods is often difficult even people have to pay for it. The Philosophy of mottainai and osagari tradition are a solution for Japanese people to deal with, so these items are not wasteful. The aim of the study was to analyze Islamic values in the mottainai philosophy and osagari tradition in Japan. This research uses a qualitative approach. Data collection techniques are with observation and indepth interviews of 3 Japanese and 5 Indonesian people living in Japan as research informants. Secondary data were from books, journals, and articles that are relevant to the research theme. The results of this study show that in the tradition of mottainai and osagari, there are Islamic values that benefit human life and protect the environment. Islamic values include preventing wasteful goods with the principles of 3R (Re-use, Reduce, and Recycle) and osagari by giving second hand goods to those who need them. The osagari tradition is a medium of communication, helping each other, and maintaining friendship. The tradition takes place across cultures, which is carried out not only by fellow Japanese, but also Japanese with non-Japanese and even among non-Japanese people living in Japan.